2016
DOI: 10.19070/2326-3350-1600051
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Quality and Safety of Energy Drink Available in the Local Markets in Saudi Arabia

Abstract: A Energy drinks have become a popular beverage worldwide. The global market for energy drink has gained momentum in the past decade, and demand is increasing every year. The objective of this study was to evaluate the microbiological quality and safety of commercial energy drinks available in the local stores in Saudi Arabia. Total bacterial count, coliform, Escherichia coli, Salmonella, and Staphylococcus aureus were included in this analysis. Out of a total of 20 tested energy drinks, microbial contamination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
5
1
Order By: Relevance
“…The present finding indicated the presence of S. aureus in products from Saud-Arabia (8.2%) as the counter zero reports of Aljaloud et al in energy drink [29]. This could be either due to differences in the types of studied product, and multiplication of the few microbial present in product during packaging, while distance transportation of the products to Ethiopia [30].…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…The present finding indicated the presence of S. aureus in products from Saud-Arabia (8.2%) as the counter zero reports of Aljaloud et al in energy drink [29]. This could be either due to differences in the types of studied product, and multiplication of the few microbial present in product during packaging, while distance transportation of the products to Ethiopia [30].…”
Section: Discussioncontrasting
confidence: 60%
“…Staphylococcal count of 0 to 2.3 × 10 3 CFU/ml in juices from Dhaka City was also reported [28]. On the other hand, Aljaloud et al [29] reported absence Staphylococcus in energy drink from Raid-Saud Arabia. Cutter also suggested the use of combination of rigid packaging materials made from metal, glass or plastic provides the heat as most effective inactivating microorganisms during product processing [30].…”
Section: Discussionmentioning
confidence: 90%
“…Conversely, many dietary supplements have been recalled from the market for being contaminated with prescription drugs and/or microorganisms [ 8 , 12 14 ]. Although the SFDA requires the manufacturers of dietary supplements to provide evidence that proves the safety and purity of their preparations besides examining a sample of the new products in the SFDA laboratories, some products were found to be contaminated with microorganisms after being approved and marketed [ 15 ]. For example, some weight loss products were found to be contaminated with aliphatic amine stimulants, such as 1,3-dimethylamylamine, which has been implicated with several cases of cerebral hemorrhage and cardiac arrest [ 16 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In line with this study, commercial carbonated water has been analysed elsewhere (Saleh et al, 2008) and no bacteria were detected in the water. In another study by Aljaloud (2016) on commercial non-alcoholic energy drinks, it was found that most of the carbonated energy drinks analysed did not contain harmful bacteria and total bacterial counts for most of the samples were less than 1 log CFU/mL). As pointed out by Ashurst (2009), the main factor in determining shelf life for carbonated beverages, is the retention of carbon-dioxide in finished products.…”
Section: Resultsmentioning
confidence: 94%